Influence of the Branched Structure of Polyoxyethylene Units in Nonionic Surfactants on the Wettability of Anthracite: A Combined Modeling and Experimental Study - Xuanlai Chen; Guochao Yan; Guang Xu; Xianglin Yang; Jiajun Li; Xuyang Bai (Adsorption Science & Technology)
Coal dust is a significant concern to the safety of coal mine operations. The wettability of coal can be effectively altered by adding surfactants to water. The development of high-efficiency dust suppressants is hampered by a lack of understanding of the microscopic interaction process between coal dust and surfactants. In this investigation, the influence of the branched structure of the polyoxyethylene unit in nonionic surfactants on the wettability of anthracite surfaces was evaluated by combining the modeling study and experimental research. The macromolecular model of Jincheng anthracite with 55 different components (C7730H3916O133N123S25) was constructed. Lauryl polyoxyethylene ether C12(EO)20 and Tween 20 were selected. The simulation results showed that due to the branched structure of polyoxyethylene, the surface of anthracite after adsorption by Tween 20 is more hydrophilic. Further analysis found that the adsorption configuration of Tween 20 is that the hydrophilic head group covers the hydrophobic tail chain, while the adsorption configuration of C12(EO)20 is that the hydrophobic tail chain covers the hydrophilic head group. The network structure formed by Tween 20 is relatively loose, and the surface is rougher. The network structure formed by C12(EO)20 is denser. Water molecules have a higher aggregation degree near Tween 20 and stronger permeability, and more hydrogen bonds are formed. The existence state of carbon and oxygen elements on the surface of modified coal was analyzed by XPS experiment, which confirmed the adsorption structure obtained by molecular simulation.